Chapter Poteri signorili e chiese locali in Valle d'Aosta (XV secolo): d'Aosta: il caso della vallata di Cogne (secoli XIII-XV) - Corniolo, Elena (Reti Medievali E-Book, 2021)
Aim of this article is to discuss the relationship between local powers and local churches starting from a peculiar case study: Cogne's valley between XIIIth and XVth century. Set in Aosta valley, in the heart of Western Alps, this place was connected with many different local powers: the Prince of Savoy, who had the territorial control of the whole region; the bishop of Aosta, who exercised a jurisdictional power over the valley of Cogne and, as chief of the diocese, was responsible for the cure of souls of the inhabitants; the Priory of Sant'Orso, who administered the Cogne's parish. The superposition of different powers produced many conflicts, which saw the community of Cogne acting as the fourth essential protagonist. Through the analysis of heterogeneous set of documents (ecclesiastical visitations, franchises, donations), the article shows how the community was able to gain its space of action thanks to the negotiation with the different powers active on the territory.